KALIMAT MAJEMUK SETARA DALAM NOVEL RUMAH SERIBU MALAIKAT KARYA YULI BADAWI DAN HERMAWAN AKSAN - Dedi kurniawan Dedi kurniawan; Charlina '; Nursal Hakim Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research is called compound sentence equivalent in a Rumah Seribu Malaikat novels by Yuli Badawi and Hermawan Aksan .The research is know the writing of compound sentence equivalent in a Rumah Seribu Malaikat novels by Yuli Badawi and Hermawan Aksan in terms of replacement element predikat the subject , and the alignment of the elements in the form of the sentence . The Methods used is a method of descriptive qualitative with the approach . The result is this compound a an equivalent there are in a Rumah Seribu Malaikat novels by Yuli Badawi and Hermawan Aksan .The results is to known of writing compound sentence equivalent in a Rumah Seribu Malaikat novels by Yuli Badawi and Hermawan Aksan replacement have tended to elements the subject as well as having the alignment on every element in the form of the sentence.Keywords: novels, Compound Sentence Equivalent